Wybrane metody kalkulacji rezerwy IBNR - Pobłocka, Agnieszka (Selected Methods of Calculating IBNR Reserves, 2008)
The article presents four deterministic methods for estimating non-life claims which have been incured but are not reported yet. These reserves belong to non-life claims reserves which are obligatorily calculated in Poland. All methods which are presented are based on the claim experience of an insurer which can be summarized in run-off triangle. Two of the methods (chain ladder and Bomhuetter's-Freguson's method) are very popular and are widely used in practise in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 368-376